Literature Review: Teh Manis Kurang Efektif Untuk Menangani Hipoglikemia - Choeron, Rachmat Chusnul; Nofiana, Ika (Care : Jurnal Ilmiah Ilmu Kesehatan, 2024)
Among Indonesian society sweet tea is commonly recognized as an agent to help individuals experiencing hypoglycaemia before they are taken to the hospital. However, tea contains chemical compounds that can lower blood glucose levels. The aim of this study is to assess the effectiveness of sweet tea in managing hypoglycaemia. A literature review method was employed, focusing on journals related to blood sugar levels, blood glucose, postprandial, hypoglycaemia, tea, green tea, black tea, Chinese tea, hypoglycaemia management guidelines, diabetes, and emergencies. Journals were sourced from the internet and limited to the past 15 years. Based on the review results, it is known that the administration of 15 grams of oral monosaccharide glucose can increase blood glucose levels by 2.1 mmol/L in 20 minutes, while 20 grams of oral glucose can increase blood glucose levels by 3.6 mmol/L in 45 minutes. Meanwhile, the administration of 3.3 grams of green tea can decrease postprandial blood glucose levels to 88.95 mmol/dL after 2 hours, the administration catechins of green tea for 369.14 mg actually decreases postprandial blood glucose levels to 88.95±6.13 mg/dL, and the administration of 32 grams of tea extract lowers postprandial blood glucose levels to 81.0 mg/dL. The conclusion drawn is that the administration of oral glucose to hypoglycaemic patients may be less effective when given with tea because tea contains polyphenols that inhibit α-amylase and α-glucosidase, activate glycolytic enzymes, thus inhibiting the process of glucose catabolism.